(untitled) (European Journal of Pure and Applied Mathematics, 2022)
We study stability analysis of a discrete-time dynamical system of Wolbachia diffusion in mosquito populations with Allee effects on the wild mosquito population. We analyze the competition between released mosquitoes and wild mosquitos. We show local and global stabilities of the fixed points, and type of bifurcations with respect to parameters. The results are verified by numerical simulations.